TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS FROM THEIR YOUNG AGE - Madaminjonova , Feruza Madaminjon qizi (Innovative Development in Educational Activities, 2023)
Learning language is getting more developed day by day and there is a fact that if children learn it in their early age, it will be much easier process, thus in this article I am going to give reasons about this wide-spread perception.